Penerapan Finite State Machine pada Alpha Utopia Menggunakan Metode Game Development Life Cycle - Dini Destiani Siti Fatimah; Eri Satria; Fujia Hermawan (Institut Teknologi Garut, 2023)
Making games that use artificial intelligence can be a special attraction for players. Games can be used as learning media. Educational games suitable for children to play using a two-dimensional style/gameplay with lots of text or drag & drop. This research aims to make a game to introduce one of the characteristics of Indonesian culture by applying a finite state machine, an abstract machine which at a certain time can be in one of a number of finite states. A game was created and named Alpha Utopia. The game development life cycle method used consists of initiation, pre-production, production, testing, beta, release stages. The research results obtained a game with the theme of shooting objects. The design uses Unreal Engine 4 with a three-dimensional style, using Artificial Intelligence or often called Non-Player Character. Finite State Machine is implemented for making the application. Indonesian cultural elements in the form of a keris weapon are displayed on game objects as the main weapon used against enemies in the form of virus characters. The making of this game is expected to introduce Indonesian culture and serve as a learning medium for its users.